Presence of behavioural problems in previously active dogs subjected to convalescence - Olby, Sara (SLU/Dept. of Clinical Sciences (until 231231), 2017)
Behavioural problems have previously been studied in several different species. Stereotypic behaviours, defined as abnormal repetitive behaviours have mostly been studied in captive wild animals while displaced behaviours, defined as misdirected normal behaviours, mostly have been studied in companion animals. Neither stereotypic behaviours nor displaced behaviours are wanted by owners and might also indicate a lower welfare of the individual performing the behaviour. Convalescence is defined as the time while a patient is recovering from an injury or illness. For dogs, convalescence is often related to a period of lowered activity and confined space. The aim of the study was to investigate the presence of behavioural problems in previously active dogs after the onset of convalescence. An online survey was conducted on Swedish dogs used to an active life by competing or training in agility and/or rally obedience. All dogs had experienced convalescence due to a musculoskeletal injury. A total of 75 dogs were used in the results. The results showed that presence of behavioural problems, both stereotypic and displaced behaviours, increased after the onset of convalescence. A majority of the owners did not believe they got the help they wished for from the veterinarian staff regarding how they could activate their dogs during convalescence. The results indicate that previously active dogs might alter their behaviour, by starting to display new behavioural problems, in order to cope with the new situation the convalescence implicates. The altered behaviours could indicate a lowered welfare during convalescence for dogs. Most dogs displaying behavioural problems were convalescent longer than three months, indicating that time might be an important factor. However, further studies are needed in order to verify these first results as well as to clarify if the results differ between dogs of different ages, with different activity levels and of different breeds.